Colloidal properties of casein micelles suspensions as a function of pH during concentration by osmotic stressing. (October 2016) - Zhao, Zhengtao; Corredig, Milena
Abstract: The physico-chemical properties of casein micelles in milk adjusted to pH 6 and 5.6 were compared with native pH milk, as a function of concentration. Skim milk was acidified and concentrated using osmotic stressing. The apparent radius of the casein micelles, measured after redilution in their corresponding permeate, decreased with decreasing pH, but showed no differences with concentration. Furthermore, the casein micelles showed free diffusive behaviour at all three pH values; only suspensions at pH 5.6 showed hindered diffusion at 4× concentration. At protein concentrations >6% the extent of caseins dissociation increased in the acidified milk samples. The relative viscosity of the concentrated suspensions (up to 4×) was modeled according to the behaviour of colloidal hard spheres, taking into account hydrodynamic interactions. The voluminosity of the casein micelles was estimated to be 3.5 and 3.1 mg L −1 for pH 6 and 5.6, respectively. The rheological behaviour of casein suspensions at pH 6.0 could still be described as that of colloidal hard spheres. On the other hand, for casein suspensions adjusted at pH 5.6, very low maximum packing volumes were obtained using a hard sphere model. It was suggested that at this pH further rearrangements and aggregation need to occur during concentration >3×, because of dramatic changes in charge, dissociation of calcium and phosphate, a significant increase in soluble casein and the decrease in steric repulsion. Although much is known about the effect of pH on casein micelles in skim milk, very little data is available on the effect of concentration. This research contributed to a better understanding of the colloidal properties of casein suspensions as a function of pH and concentration, allowing better use of modified casein concentrates as functional ingredients. Graphical abstract: Highlights: Milk was pH-adjusted and then concentrated by osmotic stressing. The voluminosity of casein micelles decreases with decreasing pH. Casein micelles at pH 6.0 have higher maximum packing volume fraction. At pH 5.6, the voluminosity of casein micelles further decreased with concentration.